Phyticism of the Painting of Wayang Kamasan: the Struggle of Distribution Structure and Order Idealism in Fulfilling Needs Tourism Industry - I Wayan Mudana; I Nengah Wirakesuma (Journal of Social Research, 2023)
Phytism is an expression of the thoughts of capitalist society to produce duplicating ideas so that producing similar merchandise can generate economic benefits in the form of money. The timeless symbols of the great and noble tradition of wayang Kamasan painting are commodified into physical art, resulting in a struggle between the idealism of a structure that is binding and standard with the idealism of an order that deifies money. Commodification is a feature of capitalism which is able to transform objects, qualities and signs into commodities to be distributed to the market. Commodities that are distributed to the market are the consumption idealism of the tourism industry. The order practice of capitalist society that works in the realm of habitus and the capital and networks that have been built is very broad. Capital relates to the ability to duplicate, while the network seeks to distribute consumer needs with producers. The physical product of the tourism industry which is distributed to the market is in the form of market paintings, handicrafts and souvenirs. To analyze physical aesthetics, the struggle for order structure, and the production of physicalism, theories and methods are used, namely: commodification theory, cultural-industry physicalism theory, and social practice theory. Discussion: The distribution of ethical ethics discusses; capital (money power), habitus (capital society's desire), image and media. Conclusion: Kamasan wayang painting has been made into a physical art alienated from capital society to get money from the tourism industry. The form of fististic art is obscured into a similar new creativity, interchanging the structure of struggle for order and mass production. Findings: Phitism of wayang Kamasan painting is barter oriented to make money.